2006
DOI: 10.1016/j.jcrs.2006.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Secondary diffractive bifocal piggyback intraocular lens implantation

Abstract: The Acri. Twin bifocal diffractive IOL implanted in the ciliary sulcus using the piggyback technique provided pseudoaccommodation in emmetropic pseudophakic eyes. Binocular implantation of these IOLs should be performed considering the differences in light distribution of the distance-weighted IOL and the near-weighted IOL models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Given that New hydrophilic acrylic supplementary IOL N Reiter et al patients' expectation are quite high for spectacle free vision, this type of secondary intervention offers a valuable alternative for optical enhancement after cataract surgery; whether it be to correct a refractive surprise or to add a premium function such as multifocality or toricity to the primary IOL. [12][13][14][15][16] The study lenses included premium characteristics like diffractive optic (A45D) or extra addition for macular diseases (A45SML), whereas toric features are also commercially available on the same IOL platform. However, the optical properties were not relevant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Given that New hydrophilic acrylic supplementary IOL N Reiter et al patients' expectation are quite high for spectacle free vision, this type of secondary intervention offers a valuable alternative for optical enhancement after cataract surgery; whether it be to correct a refractive surprise or to add a premium function such as multifocality or toricity to the primary IOL. [12][13][14][15][16] The study lenses included premium characteristics like diffractive optic (A45D) or extra addition for macular diseases (A45SML), whereas toric features are also commercially available on the same IOL platform. However, the optical properties were not relevant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The technique was then extended to correct pseudophakic spherical 2 or astigmatic 3,4 refractive errors. Because of the position of both IOLs in the capsular bag, complications such as interlenticular opacification [5][6][7] and changes in refractive results due to shift of the second IOL 8,9 were observed. Thus, the authors recommended implanting the second IOL in the ciliary sulcus.…”
Section: J Cataract Refract Surg 2012; 38:986-991 Q 2012 Ascrs and Escrsmentioning
confidence: 99%
“…In the past, even multifocal IOLs were implanted in the sulcus to provide uncorrected near visual acuity. 8,9 However, these IOLs were not designed to be placed in the sulcus, and iris capture of the second IOL 10 or pupillary block with consequent glaucoma 11 have been reported.…”
Section: J Cataract Refract Surg 2012; 38:986-991 Q 2012 Ascrs and Escrsmentioning
confidence: 99%
“…Recently Jin et al [14] reported effective correction of residual astigmatism with placement of a toric IOL in the sulcus using an obliquely crossed cylinder technique. Alfonso et al [15] have described placing diffractive multifocal IOLs in the sulcus to provide pseudoaccommodation, and Boisvert et al [16] have developed a pediatric piggyback IOL calculator to facilitate the strategy of temporary polypseudophakia in young children by removing the anterior IOL when the eye becomes sufficiently myopic due to the expected physiologic shift in refraction.…”
Section: Piggyback Iolsmentioning
confidence: 99%